Βιβλιογραφικό σημείωμα: K. Belke, Bithynien und Hellespont, v. 1-2 [TIB 13], Wien 2020. - ΛΑΜΠΑΚΗΣ Στυλιανός (Byzantina Symmeikta, 2022)
Βιβλιογραφικό σημείωμα: K. Belke, Bithynien und Hellespont, v. 1-2 [TIB 13], Wien 2020.